Availability of healthy and unhealthy foods in modern retail outlets located in selected districts of Greater Accra Region, Ghana - Adjei, Akosua Pokua; Amevinya, Gideon Senyo; Quarpong, Wilhemina; Tandoh, Akua; Aryeetey, Richmond; Holdsworth, Michelle; Agyemang, Charles; Zotor, Francis; Laar, Matilda E.; Mensah, Kobby; Addo, Phyllis; Laryea, Dennis; et al. (Frontiers in Public Health, 2022)
Background Intake of unhealthy foods is linked to the onset of obesity and diet-related non-communicable diseases (NCDs). Availability of unhealthy (nutritionally poor) foods can influence preference, purchasing and consumption of such foods. This study determined the healthiness of foods sold at modern retail outlets- supermarkets and mini-marts in the Greater Accra Region of Ghana. Methods All modern retail outlets located in six districts of Greater Accra were eligible. Those<200m² of floor area and with permanent structures were categorised as mini-marts; and those ≥200m² as supermarkets. Shelf length of all available foods were measured. Healthiness of food was determined using two criteria - the NOVA classification and energy density of foods. Thus, ultra-processed foods or food items with >225kcal/100 g were classified as unhealthy. The ratio of the area occupied by unhealthy to healthy foods was used to determine the healthiness of modern retail outlets. Results Of 67 retail outlets assessed, 86.6% were mini-marts. 85.0% of the total shelf area was occupied by foods categorized as unhealthy (ranging from 9262m2 in Ashiaman Municipality to 41892m2 in Accra Metropolis). Refined grains/grain products were the most available, occupying 30.0% of the total food shelf space, followed by sugar-sweetened beverages (20.1% of total shelf space). The least available food group–unprocessed staples, was found in only one high income district, and occupied 0.1% of the total food shelf space. Retail outlets in two districts did not sell fresh fruits or fresh/unsalted canned vegetables. About two-thirds of food products available (n =3952) were ultra-processed. Overall, the ratio of ultra-processed-to-unprocessed foods ranged from 3 to 7 with an average (SD) of 5(2). Thus, for every healthy food, there were five ultra-processed ones in the studied retail outlets. Conclusion: This study reveals widespread availability of ultra-processed foods in modern retail outlets within the selected districts. Towards a healthier food retail environment, public health and food regulators, in partnership with other stakeholders need to institute measures that improve availability of healthy foods within supermarkets and mini-marts.